2021
DOI: 10.3389/fmicb.2021.686942
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity of a Fractionated Pistacia lentiscus Oil Against Pharyngeal and Ear Pathogens, Alone or in Combination With Antibiotics

Abstract: Previous studies have clearly demonstrated that the addition of lentisk oil (LO) to streptococcal cultures makes it possible to differentiate Streptococcus spp. into three categories with Streptococcus mitis and Streptococcus intermedius sensitive, Streptococcus pyogenes, Streptococcus agalactiae, and Streptococcus mutans partially sensitive, and Streptococcus salivarius insensitive to the product. We have investigated here whether the winterization of LO, an easy and cheap procedure that removes some of the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…In fact, the inhibitory effect was proportionate to the concentration of the added oil [46]. More recent studies have demonstrated a strong antimicrobial action of mastic against Streptococcus species and several other common pharyngeal and ear pathogens, either when administered alone or in combination with antibiotics [47]. Moreover, the effective inhibition of numerous periodontal pathogens, without exhibiting any cytotoxic effects towards cells of epithelial or mesenchymal origin, makes mastic gum an ideal antimicrobial factor for oral inflammatory diseases [48].…”
Section: Antibacterial Propertiesmentioning
confidence: 99%
“…In fact, the inhibitory effect was proportionate to the concentration of the added oil [46]. More recent studies have demonstrated a strong antimicrobial action of mastic against Streptococcus species and several other common pharyngeal and ear pathogens, either when administered alone or in combination with antibiotics [47]. Moreover, the effective inhibition of numerous periodontal pathogens, without exhibiting any cytotoxic effects towards cells of epithelial or mesenchymal origin, makes mastic gum an ideal antimicrobial factor for oral inflammatory diseases [48].…”
Section: Antibacterial Propertiesmentioning
confidence: 99%
“…lentiscus resins, particularly against Helicobacter pylori, a main cause of gastric ulcers and gastric cancers, in. Since 1995, additional antimicrobial activities exerted by P. lentiscus extracts have been reported against different Gram+ve and Gram-ve bacteria, including Salmonella enteritidis, Pseudomonas fragi, Lactobacillus plantarum, Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa, and different Streptococcus species. …”
Section: Introductionmentioning
confidence: 99%
“…Antimicrobial, including antibacterial and antifungal, activities were found in the essential oils or extracts from P. lentiscus leaf, berry and bark, P. atlantica mastic gum, and P. atlantica leaf and fruit [ 20 , 21 , 23 , 28 , 29 , 30 ]. Antioxidant activity has been reported in P. atlantica subsp.…”
Section: Introductionmentioning
confidence: 99%